Photo-physiological mechanisms of tolerant difference to high temperature between two varieties of Celosia cristata - ZHANG Kai-ming; LI Yong-hua; KONG De-zheng; HE Song-lin (浙江大学学报. 农业与生命科学版, 2011)
Photo-physiological mechanisms of tolerant difference to high temperature between two varieties of Celosia cristata, Century green and Century copper were investigated. The parameters of gas exchange, chlorophyll content, light energy utilization and distribution were measured. The results showed that, Century green had higher chlorophyll a (chla) content, which made more energy distribute to quantum yield of photosystem Ⅱ (ΦPS Ⅱ). Meanwhile, higher non-photochemical fluorescence quenching associated with state transitions (qT) in Century green helped to dissipate excessive light energy timely. Century copper had a higher tolerance to high light, but photoinhibition happened under high temperature for non-stomatal factors, which reduced light energy utilization. Meanwhile, Century copper can not dissipate excessive light energy because of lower chla content and lower proportion of qT. As a result, Century copper was more sensitive to high temperature than Century green.